PROFIL HAMBATAN BELAJAR EPISTIMOLOGIS SISWA PADA MATERI ASAS BERNOULLI KELAS XI SMA BERBASIS ANALISIS TES KEMAMPUAN RESPONDEN - Gita Wahyu Pebriyanti; Harun Imansyah; A. F. C. Wijaya; Heni Rusnayati (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2017)
Based on previous research through the questionnaire and test in one of the High School in Bandung, more than 50% of students experienced epistemological learning obstacles on the dynamic fluid material and 66,2% students couldn’t answer the test about Bernoulli’s principle. The aim of this study is to identify the student’s epistemological learning obstacles profile of grade XI Bernoulli’s principle material, based on the respondent’s ability test. Epistemological learning obstacles occur due to limitation of knowledge to a certain concept and it will lead to obstacles in using their knowledge when facing different concept. The method is qualitative descriptive, combined with the historical approach analysis through the respondent’s ability test in the form of three essays covering essential concepts of Bernoulli’s principle, which given to the students in one of the High School in Bandung. The average score 68,27% is the students who experienced obstacles about Bernoulli’s equation in Torricelli’s principle, 95,36% is the students facing obstacles about Bernoulli’s equation in Venturi’s principle, and 87,05% the students obstacles on Bernoulli’s principle in aircraft lift force. The conclusion is the encounter of epistemological learning obstacles on Bernoulli’s principle material, there must be effort to minimize learning obstacles. Keywords: Learning obstacles, Bernoulli's principle, Respondent's Ability Test.